2009
DOI: 10.1177/000313480907501206
|View full text |Cite
|
Sign up to set email alerts
|

Volvulus of the Small Bowel in Adults

Abstract: The volvulus of the small bowel is a surgical emergency, causing small bowel obstruction. We performed a retrospective study of all the patients diagnosed and treated with small bowel volvulus between 1977 and 2007 at our institution. One hundred twenty-nine patients were analyzed. Thirty-nine patients presented primary volvulus and 90 secondary ones. The most frequent symptom was sudden abdominal pain. CT scan was the best diagnostic method with an accuracy of 83 per cent. Necrotic small bowel loops appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 8 publications
3
31
0
2
Order By: Relevance
“…Secondary SBV, on the other hand, has been attributed to acquired conditions: most commonly post-operative adhesions, tumours, congenital anatomic anomalies and internal hernias 2 5 6. Rarely, it can come about as a complication of intestinal malrotation in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary SBV, on the other hand, has been attributed to acquired conditions: most commonly post-operative adhesions, tumours, congenital anatomic anomalies and internal hernias 2 5 6. Rarely, it can come about as a complication of intestinal malrotation in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cases reported so far, some of them have reported that this devolution is often the only manoeuvre needed. However, given a reported 3.5% recurrence rate,6 some authors have advocated that some form of intestinal fixation or even resection of that redundant loop of small bowel be undertaken as well to avoid recurrence 2…”
Section: Discussionmentioning
confidence: 99%
“…Otra es la teoría anatómica, la cual refiere que, en las poblaciones de alto riesgo, el mesenterio correspondiente al intestino delgado es más largo, con una inserción más estrecha y una falta de grasa mesentérica 10 . Por otro lado, el vólvulo secundario del intestino medio en el que hay una lesión preexistente aparece habitualmente en los pacientes de más edad (de sexta a octava décadas de vida) 14 . La causa más frecuente es la adhesión postoperatoria.…”
Section: Discussionunclassified
“…El vólvulo clínicamente asumido y radiológicamente demostrado requiere intervención quirúrgica inmediata debido al riesgo asociado de isquemia intestinal. La desvolvulación del intestino involucrado con frecuencia es la única maniobra que hay que realizar, aunque algunos autores recomiendan la fijación intestinal o incluso la resección para evitar la recurrencia del vólvulo 8,14,37 . A casi la mitad de los pacientes se les hará una resección de un intestino delgado gangrenoso 33 .…”
Section: Discussionunclassified
“…However, it accounts for 20–35% of small bowel obstructions in Asia, Africa, and the Middle East. A precipitating factor may be the ingestion of a large amount of fiber after extended periods of fasting during the Ramadan festival [ 1 3 ]. SBV may be primary, without any underlying anatomic abnormalities or known predisposing factors.…”
Section: Introductionmentioning
confidence: 99%